Environmental Culture Exploration In The Novel "The Shark Caller By Zillah Bethel - Azzahra, Adela; Harpriyanti , Haswinda; Anita, Anita (Cultural Narratives, 2024)
This Study analyze the novel The Shark Caller with study literary ecology, describing How interaction between ecosystem natural with man. Focusing How interaction culture used For call shark . As for goals study are identify culture can influence sustainability creature life in the novel The Shark Caller, identify that's all the Shark Summoner did use culture tradition, in the novel The Shark Caller, and Analyze the cultural tradition that influence to ecosystem sea in the novel The Shark Caller. Method used in study This is descriptive qualitative, that is approach purposeful research. For describe and describe existing phenomena. Then the study is used for analyzing is ecology environment. Source research selected data is the novel The Shark Caller by Zillah Bethell. For describe the results of the novel used technique read note . The research results are described explained results as (1) describes ecology environment (2) interaction ecosystem between sharks and humans (3) impact interaction humans and sharks. And with interactions that occur between shark with man showing results impact negative and positive, with results achievement ideal ecosystem.